JUMLAH TANGGUNGAN SEBAGAI PEMODERASI PENGARUH PENGALAMAN USAHA DAN PENDAPATAN UMKM PADA KOLEKTIBILITAS KUR MIKRO BRI - Windariani, Ni Luh Ayu; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2017)
ABSTRACT The purpose of this study was to determine the effect of business experience and income of SMEs in the collectibility of credit payment with the household size as moderating variable. The sample used in this study are the debtor of Kredit Usaha Rakyat (KUR) at BRI Units Sudirman. The sample is determined by proportional random sampling in order to obtain 82 samples. Data were collected through survey method , with a questionnaire as the instrument. Data analysis technique used is Moderated Regression Analysis (MRA). The analysis showed, the longer business experience does not guarantee the improvement of credit collectibility. The higher income of SME s, can increase loan collectibility payment . Household size is able to decrease the negative influence of business experience in the collectibility of the loans payment and the household size can decrease the positive effect on the SME s income to collectibility of the loans payment .
Keywords: Keywords : Experience, Income, Household Size, Collectibility, KUR